Membangun keluarga sakinah : perspektif al-quran - Zakky, Muhammad (Maliki Interdisciplinary Journal, 2026)
The high divorce rate in Indonesia indicates that many families have not been able to achieve a harmonious and stable household life. The Qur'an provides the concept of a peaceful and loving family as a foundation for building a peaceful, loving family capable of resolving conflicts wisely. This article discusses the elements that form a peaceful family, such as selecting an ideal partner, instilling religious values, effective communication, an attitude of contentment, and justice within the family. Furthermore, the article also examines the characteristics of a peaceful family as emphasized in the Qur'an, ranging from straightening intentions, strengthening relationships with God, to developing an attitude of patience and gratitude in domestic life. This study shows that the concept of a peaceful family is not only spiritual, but also practical and relevant to address the challenges of married life in the modern era. By understanding these principles, Muslim families are expected to be able to build a harmonious and happy life and be able to apply the elements of a peaceful family according to the Qur'an.